Rapa Nui: Tradition, modernity and alterglobalization in intercultural education - Fidel Molina (Ra Ximhai, 2013)
In this research are described, analyze and compare the manifestations of the intercultural education in a difficult situation as it is Rapa Nui Island (Easter Island), traditionally isolated, in the “navel of the world” (Te pito o Te Henua), but “discovered” and assimilated by the western people and recoveredfor the intercultural idea that it surpasses this assimilation and/or global homogenization, in a alterglobalization context. We have analyzed four depth interviews and two biographical stories (lifehistories), dividing of the hypothesis of the necessity of a clear link between interculturality and education, to rethink the identity and the cultural continuity of their citizens. The obtained results suggest them programs of immersion in the school are not sufficient if they do not go accompanied of a holistic institutional work in the diverse scopes: cultural, educative, economic, environmental politician, leisure, etc. The construction of the identity sends again to individual and collective scopes, with the participation of the subject and the community. In this sense, intergenerational solidarity plays a fundamental role.